International business negotiations : a study in India - Kapoor, Ashok (New York : New York University Press ; London : University of London Press, 1970)
This book provides an in-depth examination of the negotiation process between foreign companies and the government of a developing nation - India focusing on the dynamics of the negotiation process. Reasons for the failure of these negotiations and guidelines on international government-business negotiations are presented.
Includes index.
Includes bibliographical references: p. 345-352.
lje 18/01/2018
Loans
Keywords: International business enterprises; Investments, Foreign; Investments, American; Fertilizer industry; India